En torno a la expresión de la «hombría» del esclavo y del cimarrón en dos conjuntos monumentarios en Santiago de Cuba - Carlos A. Lloga Domínguez (Études Caribéennes)
The present article examines «manhood» as a category connected to the image of the slave and the cimarrón in Cuba. It analyzes two monuments located in Santiago de Cuba, as samples of the particular expression that such association assumes in the cultural environment of East Cuba. The text explores how representations of genre are articulated with the political history in the process of re-signifying the past though art. Furthermore, the two monuments are compared in order to highlight the different expressions assumed by «manhood» as mechanisms of legitimation of hegemonic masculinity.